Case Report of a Triplet Pregnancy with Complete Hydatidiform Mole and Coexisting Twins - Marjorie H. Thompson; Nathaniel R. Miller; Shelby L. Haugan; Michael C. Gordon (Hindawi Limited, 2022)
Background. Triplet pregnancy with complete hydatidiform mole and coexisting twin fetuses is extremely rare with an unknown incidence. Case. Here, we present a case report of a pregnancy with twin fetuses and concurrent hydatidiform mole that resulted in the preterm delivery of one viable baby, the unfortunate intrauterine demise of the other twin, and successful treatment of gestational trophoblastic neoplasia in the postpartum period. Conclusion. This case highlights several important questions that arise for women who choose to carry a multiple gestation pregnancy with complete hydatidiform mole and describes complications that can occur. It is imperative to accurately assess risks and counsel individuals who elect to carry these pregnancies to provide the best possible outcomes.